The Role of N-Acetylcysteine in Obsessive-Compulsive (OCD) and Related Disorders. (1st June 2022) - Sá Couto, J.; Rodrigues, J.; Pão Trigo, M.; Da Luz, B.; Ventura Gil, T.
Abstract : Introduction: N-acetylcysteine is known for its uses in non-psychiatric conditions, such as paracetamol overdose and as a mucolytic. The rationale for its administration in psychiatric conditions is based on its ability reducing synaptic glutamate release, which was found to be increased in the cerebrospinal fluid of OCD patients. Objectives: Evaluating N-acetylcysteine efficacy in OCD symptoms. Studying mechanisms underlying its action. Identifying the frequency of side effects. Methods: PubMed database search, with the "N-acetylcysteine obsessive compulsive" keyword expression. The search was restricted to English-only articles, published in the last ten years. Twenty-five results among the best match correspondence were selected. Reference lists of articles were reviewed to identify additional articles. Results: Oliver et al. found that a daily dose of 2.400 to 3.000 milligrams of N-acetylcysteine reduced the severity of obsessive-compulsive symptoms with minimal side effects; Smith et al. found inconclusive evidence on its efficacy. A clinical trial from Ghazinadeh et al. revealed N-acetylcysteine to be effective as an add-on to citalopram, reducing the score of resistance/control to obsessions after supplementing with N-acetylcysteine. Costa et al. found out it was superior to placebo in anxiety control as a secondary outcome. Conclusions: The potential efficacy of N-acetylcysteine in the treatment of psychiatric disorders attracted interest. Mixed evidence was found that N-acetylcysteine may have some benefits controlling compulsions, both as an adjunctive as and as monotherapy. Thus, larger and more robust studies are required to further investigate the clinical effectiveness of N-acetylcysteine in this area. Disclosure: No significant relationships.